The Influence of Intellectual Capital on the Performance of Employees: A Case Study of PT BPR Syariah Bangun Drajat Warga - Nur Syarifuddin; Jauhar Faradis (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
The performance of employees is very influential for the success of an organization or company. To achieve the company goals, every company needs good performance from employees, both quality and quantity. This research was conducted to analyze how the influence of intellectual capital, consisting of human capital, structural capital, and customer capital, to the performance of employees of PT BPR Syariah Bangun Drajat Warga. This research uses the saturated sampling technique, which utilized all employees of PT BPR Syariah Bangun Drajat Warga as samples. This research uses primary data obtained from the survey using questionnaires and interviews. The data analysis methods in this research are validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis using IBM SPSS Statistics 19. The results show that human capital and structural capital do not have a significant positive influence on the performance of employees. However, customer capital has a significant positive influence on the performance of employees.